مهارة الاستماع ومعايير الجودة في التراث العربي / Listening Skill and Standards of quality in Arabic tradition - (Jasem ‘Ali Jaseem), جاسم علي جاسم (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2015)
ملخص البحث: يعد الاستماع مهارة لغوية إيجابية، وهي أولى المهارات اللغوية اكتساباً لدى الإنسان، منذ أن يكون جنيناً. وله أهمية بالغة في تعلم اللغة وتعليمها، ودوره حيوي وفعال في اكتسابها، على العكس مما تراه طريقة النحو والترجمة التي تهمل هذه المهارة إهمالاً بيِّناً؛ لأن من لا يستمع جيداً لا يمكن أن يكتسب أياً من مهارات اللغة الأخرى. والهدف من البحث هو بيان إيجابية مهارة الاستماع، وأسبقية العلماء العرب القدامى في الحديث عن جودته وبيان معاييره. وبيّنت النتائج أن الاستماع مهارة إيجابية، وله ثلاثة أنواع، هي: الاستماع للتعليم، والتصحيح، والترديد. وهناك أربعة مفاهيم له، هي: السماع، والاستماع، والإنصات، والإصغاء. ومن معايير جودته: إمهال المتكلم حتى ينتهي من الكلام، والإقبال نحوه، والوعي لما يقوله، والإصغاء لكلامه. الكلمات المفتاحية: التراث- الاستماع- الجودة- العربي- مهارة. Abstract: Listening skill is considered as a positive language skill since it’s the first skill which man acquires when he was a little. Thus, it occupies a significant position in teaching, learning and acquiring a language. On the contrary, the grammar and translation method neglect this skill. A person, who does not listen well, will not acquire any other language skills perfectly. The aim of this paper is to indicate that the positive role of listening skill was highlighted and discussed by traditional Arabic scholars before. Among the conclusions of the study: listening skill is a commendable skill that has a number of categories: listening to a teaching, correcting and repeating. It has also four notions: unintentional listening, intentional listening, focused listening and enthusiastic listening. The standards of quality for listening are: giving the speaker opportunity to finish talking, facing towards him, paying attention to what he is saying, and becoming interested in his talk. Keywords: tradition- listening- quality- Arabic- skill. Abstrak: Kemahiran mendengar dianggap satu kemahiran bahasa kerana ia adalah merupakan kebolehan pertama yang diperolehi manusia ketika kecilnya. Ini menjadikannya penting dalam konteks pembelajaran, pengajaran danpemerolehan bahasa. Sebaliknya, kaedah seperti tatabahasa dan terjemahan mengabaikan kemahiran ini. Seseorang yang tidak mendengar dengan baik tidak akan dapat menguasai bahasa dengan baik. Tujuan kertas ini ialah untuk menunjukkan peranan positif kemahiran mendengar yang telah dikupas sebelum ini oleh para cendiakiawan tradisional Arab. Di antara kesimpulan-kesimpulannya ialah: kemahiran mendengar adalah satu kemahiran yang penting yang mempunyai tiga kategori: mendengar kepada sesuatu pengajaran, membetulkan kesilapan dan mengulang beberapa kali apa yang didengar. Ia terbahagi kepada empat teras: mendengar yang tidak sengaja, mendengar dengan sengaja, mendengar dengan perhatian dan mendengar dengar minat. Piawayan kualiti kemahiran mendengar akan dicapai dengan: memberi ruang kepada penutur menghabiskan bicaranya; menghadap penutur; memberikan perhatian kepadanya dan menunjukkan minat terhadap bicaranya. Kata kunci: tradisi – mendengar – kualiti – Arab – kemahiran